Western blotting of high and low molecular weight proteins using heat - Kurien, Biji T. (Methods Mol Biol, 2015)
A method for the electrophoretic transfer of high and low molecular weight proteins to nitrocellulose membranes following sodium dodecyl sulfate (SDS) polyacrylamide gel is described here. The transfer was performed with heated (70-75°C) normal transfer buffer from which methanol had been omitted. Complete transfer of high and low molecular weight antigens (molecular weight protein standards, a purified protein, and proteins from a human tissue extract) could be carried out in 10 minutes for a 7% (0.75 mm) SDS polyacrylamide gel. For 10 and 12.5% gels (0.75 mm) the corresponding time was 15 minutes. A complete transfer could be carried out in 20 minutes for 7, 10 and 12.5% gels (1.5 mm gels). The permeability of the gel is increased by heat, such that the proteins trapped in the polyacrylamide gel matrix can be easily transferred to the membrane. The heat mediated transfer method was compared with a conventional transfer protocol, under similar conditions. The conventional method transferred minimal low molecular weight proteins while retaining most of the high molecular weight proteins in the gel. In summary, this procedure is particularly useful for the transfer of high molecular weight proteins, very rapid and avoids the use of methanol.